2020
DOI: 10.1073/pnas.1919204117
|View full text |Cite
|
Sign up to set email alerts
|

The miR-9b microRNA mediates dimorphism and development of wing in aphids

Abstract: Wing dimorphism is a phenomenon of phenotypic plasticity in aphid dispersal. However, the signal transduction for perceiving environmental cues (e.g., crowding) and the regulation mechanism remain elusive. Here, we found that aci-miR-9b was the only down-regulated microRNA (miRNA) in both crowding-induced wing dimorphism and during wing development in the brown citrus aphid Aphis citricidus. We determined a targeted regulatory relationship between aci-miR-9b and an ABC transporter (AcABCG4). Inhibition of aci-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 34 publications
0
84
0
Order By: Relevance
“…Wing dimorphism is a phenomenon of phenotypic plasticity associated with aphid dispersal. Aphids have been demonstrated to have high phenotypic plasticity and can transform from wingless to winged forms under conditions of over-crowding, lack of nutrition, and interactions with other organisms (Shang et al, 2020b ). Diverse processes take place during wing dimorphism and development (Zhang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Wing dimorphism is a phenomenon of phenotypic plasticity associated with aphid dispersal. Aphids have been demonstrated to have high phenotypic plasticity and can transform from wingless to winged forms under conditions of over-crowding, lack of nutrition, and interactions with other organisms (Shang et al, 2020b ). Diverse processes take place during wing dimorphism and development (Zhang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Diverse processes take place during wing dimorphism and development (Zhang et al, 2019 ). Many studies focused on the regulatory mechanism of wing dimorphism and development (Xu et al, 2015 ; Song et al, 2018 ; Shang et al, 2020b ). Finally, 390 of these DEGs also showed differences in the last ecdysis process from 4th instar nymph to wingless adult, and 1,887 genes only showed differences between winged and wingless adults.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that miRNAs play roles in a complex regulatory system for biological processes [ 21 , 22 , 23 , 24 , 25 , 26 ]. In insects, miRNAs are involved in the regulation of growth, metamorphosis and reproduction [ 27 , 28 , 29 , 30 , 31 , 32 ]. For instance, multiple miRNAs jointly regulate the metamorphosis development via the biosynthesis of 20E in Chilo suppressalis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%